Modified expressions of field and thermionic-field emission for Schottky barrier diodes in the reverse regime - Latreche, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
In this theoretical work, the author has modified the current-voltage relationship of the field and thermionic–field emission models developed by Padovani and Stratton for the Schottky barrier diodes in the reverse bias conditions with account of the image force correction. Considered in this approach is the shape of the Schottky barrier as a trapezoid. The obtained results show a good agreement between current densities calculated within the framework of these developed models and those calculated using the general model. У цій теоретичній роботі автор модифікував співвідношення струм-напруга у моделях польового та термоіонно-польового випромінювання, розроблених Падовані та Страттоном для бар’єрних діодів Шотткі в умовах зворотного зміщення з урахуванням корекції сил зображення. У цьому підході розглянуто форму бар’єра Шотткі як трапецієподібну. Отримані результати добре узгоджуються з густинами струму, розрахованими в рамках цих розроблених моделей та тими, що розраховуються за загальною моделлю.